2022
DOI: 10.3389/fimmu.2022.932393
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine competent gut-joint migratory T Cells contribute to inflammation in the joint

Abstract: Although studies have identified the presence of gut-associated cells in the enthesis of joints affected by spondylarthritis (SpA), a direct link through cellular transit between the gut and joint has yet to be formally demonstrated. Using KikGR transgenic mice to label in situ and track cellular trafficking from the distal colon to the joint under inflammatory conditions of both the gut and joint, we demonstrate bona-fide gut-joint trafficking of T cells from the colon epithelium, also called intraepithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Another limitation is that, although systemic IL-17 levels were higher in patients with SpA with gut inflammation, we did not prove a causal relationship with joint pathology. A recent study, however, demonstrated gut-joint trafficking of intraepithelial T cells in a tumor necrosis factor-driven SpA model (39), supporting the idea that mucosal IL-17 potentially contributes to arthritis. Future work is required to formally assess this, including in IL-23-driven models, which are also characterized by a dominant γδ-T cell-driven IL-17 response (40).…”
Section: Discussionmentioning
confidence: 84%
“…Another limitation is that, although systemic IL-17 levels were higher in patients with SpA with gut inflammation, we did not prove a causal relationship with joint pathology. A recent study, however, demonstrated gut-joint trafficking of intraepithelial T cells in a tumor necrosis factor-driven SpA model (39), supporting the idea that mucosal IL-17 potentially contributes to arthritis. Future work is required to formally assess this, including in IL-23-driven models, which are also characterized by a dominant γδ-T cell-driven IL-17 response (40).…”
Section: Discussionmentioning
confidence: 84%
“…KikGR as a photoconvertible Green-to-Red fluorescent protein has been used to label and track cell migration in different disease models, such as spondylarthritis 68 , skin infection 69 , 70 , tumor 71 , etc. In this study, CX3CR1-KikGR transgenic mice were generated and used to specifically track the migration of splenic CX3CR1 + cells from the spleen to the fibrotic liver in vivo (Figure 6 A-L and S18C-G).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both IBD and SpA are diseases characterized by changes in microbial community structure, composition, and function, termed ‘dysbiosis,’ which is suggested to prime mucosal immune cells, which traffic from the gut to the joints and cause inflammation (Gracey et al , 2020 ; Qaiyum et al , 2021 ). Photoactivatable transgenic Kaede and KikGR mice have provided evidence for trafficking of intestinal immune cells to extraintestinal sites including the joints, and gut‐joint trafficking of colonic intraepithelial lymphocytes was demonstrated in TNF ΔARE mice (Morton et al , 2014 ; Lefferts et al , 2022 ). Despite various experimental findings supporting a causal link between gut and joint inflammation, it remains unclear whether joint inflammation is critically dependent on microbial triggers or inflammatory cues from the gut.…”
Section: Discussionmentioning
confidence: 99%